Pelatihan Pengembangan Media Pembelajaran Digital E-book Menggunakan Flipbook PDF Professional bagi Guru di Kota Banjarmasin - Andi Ichsan Mahardika; Novan Alkaf Bahraini Saputra; Amirul Azis Ansari Muda; Ahmad Riduan; Nana Sophia Lazuardi; Nurmalinda (Yayasan Kawanad, 2022)
Currently, teaching materials are needed that can be accessed offline and online to make it easier for students and teachers such as e-books. e-books can be further developed with interactive features. The results of observations on a number of teachers show that teachers have not been able to create digital learning media for them to use in learning. This community service aims to improve the ability of teachers to develop digital learning media using the Flipbook PDF Professional software which will be hosted on Google Drive. This activity was carried out at the Madani Islamic High School, Banjarmasin City. The methods used in the training include stages (1) planning, (2) implementation, and (3) evaluation of activities. The results of the implementation and evaluation of activities show that training on the development of digital learning media using flipbook PDF Professional software for teachers in the city of Banjarmasin has had a positive impact on participants in the form of increasing their ability to develop learning media digitally. The positive response to the implementation of the training shows that training on the development of digital learning media into e-books is considered useful for use in the learning process in the digital era at this time.